The palaeoenvironmental potential of the eastern Jordanian desert basins (Qe'an). (20th October 2022) - Jones, Matthew D.; Richter, Tobias; Rollefson, Gary; Rowan, Yorke; Roe, Joe; Toms, Phillip; Wood, Jamie; Wasse, Alexander; Ikram, Haroon; Williams, Matthew; AlShdaifat, Ahmad; Pedersen, Patrick Nørskov; et al.
Abstract: This paper presents a summary of work undertaken by the authors and their teams on a series of Qe'an (plural of Qa'), in the Badia of eastern Jordan. These basins are foci for settlement in the region, with the sites described here (Shubayqa, Wisad and the Qa' Qattafi) edged by archaeological sites dating from the late Epipalaeolithic (ca. 14, 500 - 11, 600 cal BP) and the Neolithic (ca. 11, 700 - 6100 cal BP), and in areas still used by people today as seasonal wetlands for watering animals and growing cereal. We assess here the potential for the Qe'an sediments to provide what would be rare continuous palaeoenvironmental records for this part of SW Asia. The paper presents the first dates from the Qe'an of this region and the outline sedimentology. Much of the fill is of Holocene age, which leads to discussion of climate and landscape change over the last 15, 000 years, particularly due to the close geographical relationship between these basins and archaeology. Our optically stimulated luminescence and radiocarbon dating of the basin fill suggests that there was significantly more space in the landscape for water storage in the early Holocene, which may have therefore provided this resource for people and their livestock or game for a longer duration each year than that seen today. Linked to this are hypotheses of a more vegetated landscape during this time period. Given the environmentally marginal nature of our study area subtle changes in landscape and/or climate, and human exploitation of these resources, could have led to significant, and likely detrimental for its inhabitants, environmental impacts for the region, such as desertification. Our data are suggestive of desertification occurring, and sets up a clear hypothesis for testing by future work in the region.